2007
DOI: 10.2466/pms.104.1.277-286
|View full text |Cite
|
Sign up to set email alerts
|

Morning and Evening Personality Characteristics in a Sample of Young Italians

Abstract: The goal of this study was to investigate associations of morning and evening personality types with personality dimensions in a convenient sample of 60 men and 60 women, ages 18 to 29 years. A short form of the Morningness-Eveningness Questionnaire and a personality questionnaire Come mi vedo (How I see myself), based on the 5-factor model of personality, were given. Several personality dimensions appear to be significantly correlated with Morningness scores: Conscientiousness (positively) and Openmindedness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…Energy is called Extraversion in other questionnaires based on the Big Five model, such as the NEO-PI by Costa and McCrae, and is a personality factor concerning parameters of assertiveness, activity, positive emotion, and gregariousness, similar to those concerning the factor Extraversion. Moreover, our results reveal a higher percentage of subjects with intermediate disposition; these data can be compared to previous studies reporting higher percentages of intermediate types [48], though with exceptions, and, usually, lower percentages of Morning and Evening types, depending on the samples explored [49,53,56,57]. …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Energy is called Extraversion in other questionnaires based on the Big Five model, such as the NEO-PI by Costa and McCrae, and is a personality factor concerning parameters of assertiveness, activity, positive emotion, and gregariousness, similar to those concerning the factor Extraversion. Moreover, our results reveal a higher percentage of subjects with intermediate disposition; these data can be compared to previous studies reporting higher percentages of intermediate types [48], though with exceptions, and, usually, lower percentages of Morning and Evening types, depending on the samples explored [49,53,56,57]. …”
Section: Discussionsupporting
confidence: 75%
“…Our data can be compared to previous research, which reported that Evening types usually score higher on Impulsivity, Neuroticism, Sociability, and Psychoticism [41,52] and Morning types score higher on Conscientiousness [53]. Unlike other research [53], in our sample, Morning types scored higher on Openness to Culture. Morningness-Eveningness disposition can also have a role in Extraversion [40].…”
Section: Discussionsupporting
confidence: 53%
“…Overall, findings for the relation between circadian preference and openness are inconsistent. Some of the studies reported small negative correlations with morningness (Cavallera & Giampietro, 2007; Díaz-Morales, 2007; Dresch et al, 2005; Hogben, Ellis, Archer, & von Schantz, 2007; Russo, Leone, Penolazzi, & Natale, 2012; Tsaousis, 2010), whereas others reported moderate positive relations (Randler, 2008b; Zelenski et al, 2003) or no significant relation (DeYoung, Hasher, Djikic, Criger, & Peterson, 2007; Tonetti, Fabbri, & Natale, 2009). In sum, research findings do not reveal systematic relations between circadian preference and openness.…”
Section: Circadian Preference and Personalitymentioning
confidence: 99%
“…As a result of that, it has raised the interest of some linguists in this respect (De Bot -Fang, 2017). According to earlier research, morning and evening personality types can be correlated with certain personality factors such as emotional stability, trustworthiness, creativity, originality and so on (Giampietro -Cavallera, 2007a).…”
Section: Cognitive Factorsmentioning
confidence: 99%